Pengendalian Kinerja Keuangan Pemerintah Daerah Melalui Efektivitas Pelaksanaan Anggaran Pendapatan dan Belanja - Hendrawan; Warka Syachbrani (Journal of Accounting, Economics, and Business Education, 2023)
This study aim is to identify the effectiveness and efficiency of the regional revenue and expenditure budget as a means of controlling the district government, in order to improve the function of government services. The research method used was descriptive data analysis method, which is collecting data, classifying, processing and analyzing data so that an overview of the problem under study is obtained, then provides suggestions based on the conclusion. The type of data collected is qualitative data consisting of primary data and some secondary datas. This research was obtained facts about the effectiveness and efficiency of regional income and expenditure budgets as a means of government control by observing and analyzing a problem that occurs in research location regarding the existing suitability then drawing conclusions from the problem under study. Research result show that the financial performance of the Enrekang Regency Government for three years was decreased. In 2017 was categorized as less effective, in 2018 50.95% was categorized as ineffective, and in 2019 54.26% was categorized as ineffective. Meanwhile, in efficiency study shows these three years has decreased, for the Efficient value in 2017 of 11.51%, in 2018 it was 18.88%, and in 2019 it was 19.44%.